2017
DOI: 10.1039/c7cc01027c
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid molecular/enzymatic catalytic cascade for complete electro-oxidation of glycerol using a promiscuous NAD-dependent formate dehydrogenase from Candida boidinii

Abstract: Glycerol is a common fuel considered for bioenergy applications. Computational docking studies were performed on formate dehydrogenase from Candida boidinii (cbFDH) that showed that mesoxalate can bind to the buried active site of the holo form predicting that mesoxalate, a byproduct of glycerol oxidation, may act as its substrate. Spectroscopic assays and characterization by HPLC and GC/TCD have shown for the first time that cbFDH can act as a decarboxylase with mesoxalate. From this assessment, cbFDH was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Bioelectronic materials interface biology with synthetic devices by interconverting electronic and biological signals and processes. The biological components interfaced to these materials range from biomolecules , to cells , and living organisms. , By seamlessly bridging the synthetic–living interface, without significant perturbation to biological function, bioelectronic materials may improve our understanding of biological systems or even control their functionality. Bioelectronics promise to enhance and prolong human life through biomedical technologies such as implantable power sources, , wearable sensors, , therapeutic, , and prosthetic implants. , They can also harness functional biological components, such as enzymes, to enhance the sensitivity of nonbiomedical sensors as well as improve the efficiency of electrocatalytic syntheses for energy production , and pharmaceutical applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Bioelectronic materials interface biology with synthetic devices by interconverting electronic and biological signals and processes. The biological components interfaced to these materials range from biomolecules , to cells , and living organisms. , By seamlessly bridging the synthetic–living interface, without significant perturbation to biological function, bioelectronic materials may improve our understanding of biological systems or even control their functionality. Bioelectronics promise to enhance and prolong human life through biomedical technologies such as implantable power sources, , wearable sensors, , therapeutic, , and prosthetic implants. , They can also harness functional biological components, such as enzymes, to enhance the sensitivity of nonbiomedical sensors as well as improve the efficiency of electrocatalytic syntheses for energy production , and pharmaceutical applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Through this reversible reaction system, FDHs are industrially important enzymes in the regeneration of the NAD(P)H coenzyme and the reduction of CO 2 to formate, which is a stabilized form of hydrogen fuel. Studies about the biotechnological usage of FDHs have been focusing on the methylotrophic yeasts (Abdellaoui et al 2017;Junxian et al 2017;Sungrye et al 2014;Ordu et al 2013) and extremophilic microorganisms (Fogal et al 2015;Davies et al 2016;Niks et al 2016;Alissandratos et al 2013). Now, however, due to developing next-generation sequencing technologies the number of plants which have complete genome sequence information is continuously increasing.…”
Section: Introductionmentioning
confidence: 99%
“…GC–TCD can efficiently detect CO 2 formed in the headspace of an EBFC, providing more accurate results regarding how much fuel has been oxidized [ 36 , 55 ]. TCD is used to detect volatile compounds that show low response in other detectors, including UV detectors and RID.…”
Section: Analytical Techniques Employed With Ethanol Ebfcsmentioning
confidence: 99%
“…Compounds with good thermal conductivity, such as ammonia, hydrazine, and CO 2 , are the most suitable for this analytical technique and may also be applied for quantification [ 56 , 57 ]. Headspace GC–TCD has been demonstrated to detect CO 2 efficiently during complete glycerol oxidation [ 34 , 36 , 55 ]. Our research group has applied GC–TCD to identify CO 2 in a BFC containing a hybrid system based on MWCNT-COOH/pyrene-TEMPO/OxDc, which confirmed that this bi-catalytic system collected 12 electrons from ethanol by completely oxidizing it to CO 2 [ 34 ].…”
Section: Analytical Techniques Employed With Ethanol Ebfcsmentioning
confidence: 99%